Evaluation of Package C Equality Program at the Padel Community Learning Activity Center, Karueng Village, Enrekang District - Arif Efendi A.S; Sitti Mania; Muhammad Nur Akbar Rasyid (Universitas Muhammadiyah Enrekang, 2024)
The main purpose of the evaluation of the Package C Equality Education Program at the Community Learning Activity Center (PKBM) Padel Karueng Village, Enrekang District is to identify the effectiveness of the curriculum, teaching methods, and the level of participant satisfaction. The evaluation model used is a responsive evaluation model with a qualitative research approach using data collection techniques through observation, interviews, and document analysis. The results of the evaluation show that the effectiveness of the Package C curriculum at PKBM Padel has a positive impact on the achievement of learning objectives that are oriented to the needs and challenges of current education, Interactive and varied teaching methods oriented to the active participation of learning residents are also considered effective in increasing the understanding of the concept of learning residents. In addition, the satisfaction of the participants was illustrated by the inclusive atmosphere and support of the Learning Teachers as well as the active involvement of learning residents in the learning process. However, a number of aspects that need to be improved and developed in the implementation of the Package C Equality Education program at PKBM Padel Karueng Village, Enrekang District are also identified, including the need to integrate more practical activities and group discussions in teaching methods, as well as provide additional learning resources. This step is expected to increase student engagement and satisfaction, ensuring that the material is better understood and applied.